Differentiation of Documented and Justification of Judicial Opinions - Mohammad Reza kaykha; shaghayegh amerian (پژوهشهای حقوقی)
One of the principles of fair proceedings is the principle of documentary and reasoned judicial decisions. The importance of this principle is so great that its failure to be considered by the judicial authority has been identified as one of the cases of voting violations. Given that the observance of this principle has been emphasized in the constitution, civil and criminal procedure, and even as an accepted principle in quasi-judicial authorities, such as the law on handling administrative violations, the law on handling violations of the armed forces, and the tax law. is, the analysis of the nature of the words documented and substantiated to explain the difference between the two in order to resolve some ambiguities is considered one of the goals of this article. This research, which was carried out with a descriptive-analytical method, shows that the explanation of each of the two words and the purpose of the legislator regarding these words is a legal gap that is considered necessary to be addressed. Therefore, it can be said that created causation, inherent authenticity, objective process, credibility in judicial matters and the judge's responsibility to discover the facts are considered to be documentary features, and in contrast to demonstrative causality, fake authenticity, mental process, credibility in subjective matters. And the claimant's mission in this field are considered to be well-reasoned approaches.